Behavioral Economics of Crime Rates and Punishment Levels - Chiba, Saori (2016)
Empirical studies have shown, paradoxically, that increasing the probability of apprehension can correlate with an increase in the total number of criminal actions. To examine this phenomenon, we develop a dynamic model of “personal rules” in which forgetfulness and hyperbolic discounting together can cause a potential criminal to commit more crimes as the probability of apprehension increases. At the time of the future decision, he may commit a crime due to hyperbolic discounting, even if it is not profitable. Hence, he may choose not to commit a crime today as a commitment device to abstain from crime in the future. However, increased prosecution can limit the effectiveness of the commitment device.